2018–2019 Florida Citrus Production Guide: Canopy Management - Tripti Vashisth; Mongi Zekri; Fernando M. Alferez (EDIS)
This 4-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide.  Written by Tripti Vashisth, Mongi Zekri, and Fernando M. Alferez, and published by the Horticultural Sciences Department, January 2019.